Self Efficacy dan Resiliensi pada Mahasiswa yang mengalami Pembelajaran Daring: Putri Ayu Andira, Fathana Gina - Ayu Andira, Putri; Gina, Fathana (Fakultas Psikologi Universitas Bhayangkara Jakarta Raya, 2022)
The existence of this pandemic Covid-19 has an impact on some aspects like health, economy and education. This virus is spreading around the world specifically in education sector. During the Covid-19 pandemic, students around the world appliying distance learning from their home. This distance learning needs an adaptation process that making students stress in learning. Stress in learning makes many students feel pressure because a lot of assignments which causes the level of student resilience to decrease. Low resilience will make students to be anxious when facing their problems or make them depressed and make them study longer than usual. One of the factors that related to resilience is self-efficacy where resilience can increase or decrease due to self-efficacy. The purpose of this research is to find out the relationship between self- efficacy and resilience in students who experience distance learning. The technique we will use is probability sampling with a cluster random sampling approach with a research sample of 100 samples. The results showed that the correlation coefficient between self-efficacy and resilience was r= 0.499** and p= 0.000 (p<0.05). The results shows that there is a significant positive relationship between self-efficacy and resilience. The higher the self-efficacy, the higher the resilience and it goes for the other way, the lower the self-efficacy, the lower the resilience. This research leads to the ideas for further research are expected to research other factors that have a relationship with student resilience such as religion or social support.